A facile method for high-throughput screening of drug-eluting coatings in droplet microarrays based on ultrasonic spray deposition. (16th September 2021) - Wang, Cong; Xue, Yunfan; Huang, Junjie; Ren, Kefeng; Greiner, A.; Agarwal, S.; Ji, Jian
Abstract : Droplet microarrays are fabricated for the high-throughput screening of drug-eluting coatings via ultrasonic spray deposition technique. Abstract : Coating modification such as drug-eluting coating is one of the most important approaches for the functionalization of biomedical devices. However, the throughputs are limited in conventional coating methods and the concept of miniaturization is rarely fulfilled. A droplet microarray (DMA), as a unique high-throughput platform, can avoid cross-contamination and reduce the consumption of materials which is inherently suitable for coating research yet is difficult to apply with coating materials via traditional methods. Here, we bring up a facile method based on ultrasonic spray deposition to integrate coating materials into a DMA. Several common polymer materials were selected to fabricate a DMA, and the obtained DMA showed the ability to anchor water droplets and form specific patterns. Coating arrays with a typical sandwich structure were also prepared for the high-throughput screening of drug-eluting coatings to demonstrate the potential of the platform in coating research. This developed method is efficient and compatible and enriches the choices of materials that can be applied in DMAs.